Gynura procumbens: agronomic practices and future prospects in Malaysia - Mohammad Yusoff, Martini; Misran, Azizah; Ahmed, Omar Ali; Wan Majid, Wan Huda Dinie; Megat Wahab, Puteri Edaroyati; Ahmad, Nur Fatin (Universiti Putra Malaysia Press, 2019)
Good agronomic practice is a key to a successful crop production aiming at high yield and quality in small or large scale planting. Gynura procumbens (Lour.) Merr. (Family Asteraceae) is a herbal plant rich in phytochemical compounds of wellbeing benefits to the consumers. Suitable and complete technology on agronomic practices such as cultivation technique, fertilization application, water requirement, weed control and pest and disease management of G. procumbens or locally known as Sambung Nyawa for the Malaysian environment can ensure quality product and high yield. This may attract local producers and smallholders to cultivate this medicinal plant commercially. Complete technology package documented for commercial planting of G. procumbens may encourage its planting which would ensure the sustainable supply of G. procumbens raw materials for the pharmaceutical and health industries. Suitable agronomic practices adopted contribute to sustainable commercial production of G. procumbens. It endeavours to support the country's Entry Point Project under The Agriculture National Key Economic Area (NKEA) to become a potential hub for the manufacturing of high-value G. procumbens based herbal products as well as other herbal species. Therefore, it is crucial to develop and to adopt the necessary agronomic practices for the commercial cultivation for this medicinal herb to support the demand for the industry while directly increase farmers' farm profit.